New readers, new reading skills and meaning: challenges for media and information literacy - Cerigatto, Mariana Picaro [UNESP]; Silva Casarin, Helen de Castro [UNESP] (Univ Federal Campina Grande, 2015)
Recognizing the importance of developing the information and media literacy in contemporary society, this article discusses the scenario of hybrid languages born on cyberspace, hypertext and the new types of readers who interact with information, now disseminated by digital media. As theoretical references authors such as Lucia Santaella, we develop arguments that present the headquarters of language and thought within a semiotic support. Matrices help to understand the phenomenon of hybrid language in hypertext. Therefore, we emphasize that the development of skills associated with the new reading environments propitiated by the virtual environment requires the understanding of language, which is one of the concepts used within the media and information literacy (MIL) proposal of Unesco, which combines the two concepts and skills of information and media literacy. It is hoped that this article motivate scholars and practitioners of education and information to take responsibility to educate for information environments that arise with new media and technologies, emphasizing the issue of reading and language.

Ao reconhecer a importância de desenvolver a competência informacional e midiática na sociedade contemporânea, o presente artigo discute o cenário de linguagens híbridas que nasce diante o ciberespaço, o hipertexto e os novos tipos de leitores que interagem com a informação, agora disseminada pelas mídias digitais. Tendo como referenciais teóricos autores como Lucia Santaella, procuramos desenvolver argumentos que apresentem as matrizes da linguagem e do pensamento dentro de um respaldo semiótico. As matrizes ajudam a compreender o fenômeno da linguagem híbrida no hipertexto. Diante disso, enfatizamos que o desenvolvimento de habilidades ligadas aos novos ambientes de leitura propiciados pelo ambiente virtual depende da compreensão da linguagem, que é um dos conceitos trabalhados dentro da proposta de alfabetização midiática e informacional (AMI) da Unesco, que agrega as duas noções e habilidades da information e media literacy. Espera-se que este artigo motive estudiosos e profissionais da educação e informação a assumirem a responsabilidade de educar para os ambientes informacionais que surgem com as novas mídias e tecnologias, dando ênfase à questão da leitura e linguagem.
Novos leitores, novas habilidades de leitura e significação: desafios para a media e information literacy
Keywords: Hypertext; Matrices of language; Media and information literacy; Hipertexto; Matrizes da linguagem; Media e information; literacy